Fibroblast growth factor receptor 3 isoforms: Novel therapeutic targets for hepatocellular carcinoma?. Issue 6 (16th October 2015) - Paur, Jakob; Nika, Lisa; Maier, Christiane; Moscu‐Gregor, Alexander; Kostka, Julia; Huber, Daniela; Mohr, Thomas; Heffeter, Petra; Schrottmaier, Waltraud C.; Kappel, Sonja; Kandioler, Daniela; Holzmann, Klaus; et al.
Abstract : Fibroblast growth factor receptors (FGFRs) are frequently up‐regulated in subsets of hepatocellular carcinoma (HCC). Here, we provide mechanistic insight that FGFR3 splice variants IIIb and IIIc impact considerably on the malignant phenotype of HCC cells. The occurrence of FGFR3 variants was analyzed in human HCC samples. In hepatoma/hepatocarcinoma cell lines, FGFR3 isoforms were overexpressed by lentiviral constructs or down‐modulated by small interfering RNA (siRNA; affecting FGFR3‐IIIb and ‐IIIc) or an adenoviral kinase‐dead FGFR3‐IIIc construct (kdFGFR3). Elevated levels of FGFR3‐IIIb and/or ‐IIIc were found in 53% of HCC cases. FGFR3‐IIIb overexpression occurred significantly more often in primary tumors of large (pT2‐4) than of small size (pT1). Furthermore, one or both isoforms were enhanced mostly in cases with early tumor infiltration and/or recurrence at the time of surgery or follow‐up examinations. In hepatoma/hepatocarcinoma cells, up‐regulated FGFR3‐IIIb conferred an enhanced capability for proliferation. Both FGFR3‐IIIb and FGFR3‐IIIc suppressed apoptotic activity, enhanced clonogenic growth, and induced disintegration of the blood/lymph endothelium. The tumorigenicity of cells in severe combined immunodeficiency mice was augmented to a larger degree by variant IIIb than by IIIc. Conversely, siRNA targeting FGFR3 and kdFGFR3 reduced clonogenicity, anchorage‐independent growth, and disintegration of the blood/lymph endothelium in vitro . Furthermore, kdFGFR3 strongly attenuated tumor formation in vivo . Conclusions: Deregulated FGFR3 variants exhibit specific effects in the malignant progression of HCC cells. Accordingly, blockade of FGFR3‐mediated signaling may be a promising therapeutic approach to antagonize growth and malignant behavior of HCC cells.(Hepatology 2015;62:1767–1778)